2009
DOI: 10.1002/ijc.24302
|View full text |Cite
|
Sign up to set email alerts
|

FGFR4 Gly388Arg polymorphism may affect the clinical stage of patients with lung cancer by modulating the transcriptional profile of normal lung

Abstract: The association of the fibroblast growth factor receptor 4 (FGFR4) Gly388Arg polymorphism with clinical stage and overall survival in a series of 541 Italian lung adenocarcinoma (ADCA) patients indicated a significantly decreased survival in patients carrying the rare Arg388 allele as compared to that in Gly/Gly homozygous patients [hazard ratio (HR) 5 1.5; 95% confidence interval (CI) 1.1-1.9], with the decrease related to the association of the same polymorphism with clinical stage (HR 5 1.8, 95% CI 1.3-2.6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 18 publications
3
35
0
2
Order By: Relevance
“…A mixture of 1.5 ug of the biotinylated cRNA sample and Hyb E1 hybridization buffer containing 37.5% (w/w) formamide was hybridized on a mouse WG6 chip on an Illumina platform (Illumina, San Diego, CA, USA) as described. 23 Three biological and two technical replicates were performed. BRB array tool was used to identify differentially expressed genes with a detection P value o0.001.…”
Section: Microarray Analysismentioning
confidence: 99%
“…A mixture of 1.5 ug of the biotinylated cRNA sample and Hyb E1 hybridization buffer containing 37.5% (w/w) formamide was hybridized on a mouse WG6 chip on an Illumina platform (Illumina, San Diego, CA, USA) as described. 23 Three biological and two technical replicates were performed. BRB array tool was used to identify differentially expressed genes with a detection P value o0.001.…”
Section: Microarray Analysismentioning
confidence: 99%
“…A polymorphism in FGFR4 (9) characterized by conversion of guanine to adenine at position 1,217 in exon 9 results in the substitution of arginine for glycine at codon 388 in the transmembrane domain; 40% to 50% of Caucasians carry at least one copy of this allele. The FGFR4-R388 allele is associated with poor outcomes in cohorts of sarcoma (10), prostate (11), lung (12,13), and head and neck carcinomas (14) and in those with advanced and treatment-resistant breast cancer (15). The corresponding mouse SNP accelerates breast cancer progression (16).…”
Section: Introductionmentioning
confidence: 99%
“…A single-nucleotide polymorphism (SNP) in the fibroblast growth factor receptor isoform 4 gene (FGFR4), causing a conversion of guanine to adenine at position 1.217 in exon 9 (FGFR4-G388R), has been reported to associate with a worse prognosis in several human cancers (Morimoto et al 2003, Wang et al 2004, Thussbas et al 2006, da Costa Andrade et al 2007, Sasaki et al 2008, Falvella et al 2009). Serra et al (2012) showed that, in pNET patients, the FGFR4-G388R allele (assessed at germline level) associates with a tumour diameter O2 cm, local invasiveness, lymphovascular invasion, lymph node and liver metastases.…”
Section: Methodsmentioning
confidence: 99%